AB0999 Finnish cohort of patients with raynaud's phenomenon-nailfold videokapillaroskopy findings and autoantibody values. (15th June 2017) - Häme, A; Vidqvist, K-L; Parmanne, P; Puhakka, A; Hasan, T; Mäkinen, H; Panelius, J; Peltomaa, R; Perovaara, M; Luosujärvi, R
Abstract : Background: Raynaud'n phenomenon (RP) is very common all around the world, especially in cold climates (from 3 to 22%) (1). Nailfold capillaroscopy and autoantibodies have a pivotal role in diagnosing of different diseases in the context of RP (2).This is a first study of patients with RP in Finnish tertiary care hospitals. Objectives: Aim is to investigate nailfold videokapillaroskopy (NVC) findings and autoantibody-values in patients with Raynaud's phenomenon first time in Finnish prospective multicenter study cohort. Methods: We enrolled consecutive 160 patients with Raynaud's phenomenon who underwent NVC 9/2012–4/2013. Nailfold capillaries of II-V fingers of both hands were examined by using an optical probe videokapillaroskope mounted with x200 magnification lens. Images where analyzed with Videocapt software (DS Medigroup, Milan, Italy). NVC findings were classified with qualitative scoring, and early, active and late patterns were classified as"scleroderma pattern". Serum levels of antinuclear antibodies (ANA), antitopoisomerase I antibodies (anti-Scl-70) and anticentromere antibodies (ACA) were analyzed. Clinical and epidemiological features were reviewed. Results: The mean age of the patients was 50, 4 years (±14, 8 SD), range 19–81 years, and 79, 4% were female. 15, 6% of patients were smokers and 3 had diabetes. Reasons for performing of NVC can be divided into three categories: (i) assessment of disease activity in previously diagnosed scleroderma (n=26), (ii) differential diagnosis of Raynaud's phenomenon (n=98), and (iii) assessment of Raynaud's phenomenon in other rheumatic diseases (n=36). In group ii mean age was 48, 6 years (±14, 6 SD), 77, 6% were female and 17, 3% were smokers. In this group 26, 5% (n=26) were diagnosed with scleroderma or there was strong suspicion of scleroderma at the first consultation of this study, 52% (n=51) were diagnosed with primary Raynaud's phenomenon and 21, 5% (n=21) were diagnosed with some other rheumatic disease (MCTD (n=2), Sjögren's syndrome (n=3), SLE (n=4), UCTD (n=8) and rheumatic arthritis (n=4)). Among those patients who was diagnosed with scleroderma, only 4% (n=1) had normal NVC pattern, 76, 0% had scleroderma pattern (n=19) and 20, 0% (n=5) had other non-specific changes. 19, 2% (n=5) had low titers of ANA, 7, 7% (n=2) had medium titers of ANA and 76, 0% (n=19) had high titers of ANA. 69, 2% (n=18) had anticentromere antibodies (ACA) and 3, 8% (n=1) had antitopoisomerase I antibodies (anti-Scl-70). Those patients who had positive ACA or anti-Scl-70 also had a NVC scleroderma-pattern. Conclusions: The main reason for NVC in this cohort was differential diagnosis of Raynaud's phenomenon, and in most patients in diagnostic group primary Raynaud's phenomenon was diagnosed. NVC is useful method for differential diagnosis of Raynaud's phenomenon. References: Spencer-Green, George. Outcomes in primary Raynaud phenomenon: a meta-analysis of the frequency, rates, and predictors of transition to secondary diseases. Archives of internal medicine 158.6 (1998): 595–600. Ingegnoli, Francesca, et al. Improving outcome prediction of systemic sclerosis from isolated Raynaud's phenomenon: role of autoantibodies and nail-fold capillaroscopy. Rheumatology (2010): kep447. Disclosure of Interest: None declared